PLACENTA PREVIA - Duschanova, Z.A.; Jamoladdinova, A.O. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2025)
a woman's history of cesarean section, placenta previa, abortions, genital infections and extragenital diseases creates a risk of placenta previa. Prevention of abortions, timely detection and treatment of genital infections and extragenital diseases help prevent placenta previa and the resulting bleeding, as well as maternal and infant mortality.